2021
DOI: 10.1161/cir.0000000000000913
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Optimal Population Cardiovascular Health Requires an Interdisciplinary Team and a Learning Healthcare System: A Scientific Statement From the American Heart Association

Abstract: Population cardiovascular health, or improving cardiovascular health among patients and the population at large, requires a redoubling of primordial and primary prevention efforts as declines in cardiovascular disease mortality have decelerated over the past decade. Great potential exists for healthcare systems–based approaches to aid in reversing these trends. A learning healthcare system, in which population cardiovascular health metrics are measured, evaluated, intervened on, and re-evaluated, can serve as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…43 In the meantime, application of proven public health and health care interventions to maintain and improve CVH at all ages is long overdue. 40 Strategies for assessing, monitoring, and improving CVH are emerging [44][45][46] ; their accelerated dissemination and implementation are urgently needed. The current study indicates the feasibility of measuring and monitoring CVH in the US population and subgroups using NHANES, although more robust data are needed for children younger than 16 years.…”
Section: Implications For Public and Individual Healthmentioning
confidence: 99%
“…43 In the meantime, application of proven public health and health care interventions to maintain and improve CVH at all ages is long overdue. 40 Strategies for assessing, monitoring, and improving CVH are emerging [44][45][46] ; their accelerated dissemination and implementation are urgently needed. The current study indicates the feasibility of measuring and monitoring CVH in the US population and subgroups using NHANES, although more robust data are needed for children younger than 16 years.…”
Section: Implications For Public and Individual Healthmentioning
confidence: 99%
“…146 Examples of CVH data visualization tools that have been integrated with the EHR in learning health care systems include Stroke Prevention in Healthcare Delivery Environments and Priorities Wizard, among others. 147 Clinicians have the opportunity to use these tools with patients at the point of care to raise awareness of CVH and use shared decision-making approaches to help patients preserve or achieve optimal CVH. 148 For greater success, it is suggested that clinicians use motivational interviewing strategies to help patients identify those metrics that would benefit from improvement and for which the patient expresses some motivation for change and can envision the means to do so.…”
Section: Implementation Of Cvh In Clinical Practicementioning
confidence: 99%
“…These efforts have also increased awareness about the SDOH and their driving influence on CVH disparities and have provided recommendations for addressing them. 2,33,71,147,161,[188][189][190][191][192] Although interventions focused on the entire construct of CVH are exceedingly rare, health policy statements have focused on several important structural, contextual, and intergenerational factors that can promote overall optimal CVH (Table 2), including but not limited to access to quality health care, healthy foods, and recreational facilities for leisure-time PA. 193 Ongoing advocacy efforts at the federal, state, and community levels must continue for improvement in population-wide CVH. Indeed, policy-level solutions are often the only ways to address issues such as health care reform (for CVH monitoring and intervention), transformation of PA and healthy meal programs in schools, regulation of tobacco/ nicotine products, and accessibility to a healthier food supply.…”
Section: Policiesmentioning
confidence: 99%
“…Another aspect to consider is the model of patient care with HTN. Models that promote a multidisciplinary team approach tend to generate better health results (Foraker et al., 2021; Himmelfarb et al., 2016; Jardim et al., 2020), as is the case with the service where this study was carried out. In addition, the nurse in the care of people with HTN can also identify the spectrum of this CI in other NDs (such as sedentary lifestyle (00168), obesity (00232), overweight (00233)), which can reduce its frequency throughout the follow‐up.…”
Section: Discussionmentioning
confidence: 99%